2019
DOI: 10.1103/physrevb.99.064413
|View full text |Cite
|
Sign up to set email alerts
|

Flat-band spin dynamics and phonon anomalies of the saw-tooth spin-chain system Fe2O(SeO3)2

Abstract: Fe 3+ S = 5/2 ions form saw-tooth like chains along the a axis of the oxo-selenite Fe2O(SeO3)2 and an onset of long-range magnetic order is observed for temperatures below TC = 105 K. This order leads to distinct fingerprints in phonon mode linewidths and energies as resolved by Raman scattering. In addition, new excitations with small linewidths emerge below T = 150 K, and are assigned to two-magnon scattering processes with the participation of flat-band and high energy magnon branches. From this a set of ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The above calculation indicates that sawtooth chain antiferromagnet can possess magnons with nearly flat dispersion relation. In the Raman scattering study, some peaks were observed in the chain specific polarization at 6.8, 20.7, 64.8, and 76.9 meV 24 . The peaks have been interpreted as two magnon scattering from the nearly flat bands along the chain direction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The above calculation indicates that sawtooth chain antiferromagnet can possess magnons with nearly flat dispersion relation. In the Raman scattering study, some peaks were observed in the chain specific polarization at 6.8, 20.7, 64.8, and 76.9 meV 24 . The peaks have been interpreted as two magnon scattering from the nearly flat bands along the chain direction.…”
Section: Discussionmentioning
confidence: 99%
“…The Curie-Weiss fit to the temperature dependence of the magnetic susceptibility yields Weiss temperature of −200(10) K, indicating predominant antiferromagnetic interactions 25 . As the temperature is decreased below 300 K, the magnetic susceptibility deviates from the Curie-Weiss rule and shows a shoulder around 120 K 24 , 25 . The short range order should develop above the transition temperature due to the low-dimensionality in the magnetism.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…From an experimental point of view, the situation remains challenging, with only a limited number of compounds being reported up to today to materialize dominant magnetic interactions in a sawtooth pattern. Prominent examples are the delafossite YCuO 2.5 [54][55][56][57], the double spin chain systems KCuCl 3 and TlCuCl 3 [19], the multiferroic Mn 2 GeO 4 [58][59][60], the olivines ZnL 2 S 4 (L = Er, Tm, Yb) [61], and the Fe chains Rb 2 Fe 2 O(AsO 4 ) 2 and Fe 2 O(SeO 3 ) 2 [62,63]. Remarkably, and despite great efforts, a magnetization plateau has not been reported for any of these systems.…”
Section: Introductionmentioning
confidence: 99%